Dynamic fluorescent anti-counterfeit label material as well as preparation method and application thereof
By adjusting the ratio of ytterbium and erbium, a dynamic fluorescent anti-counterfeiting label material is prepared, which solves the problems of weak recognition ability and poor stability of existing lanthanide-doped upconversion luminescent materials, and realizes the luminescence color transition from red to green. , which improves the identification and stability of anti-counterfeiting materials and is suitable for mass production.
Patent Information
- Application Number
- CN202411431645.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-21
AI Technical Summary
The existing lanthanide doped upconverted luminescent anti-counterfeiting materials have problems such as weak identification ability and weak stability, which limits their practical application in the field of anti-counterfeiting.
By adjusting the proportion of chloride, chloride and chloride, prepare dynamic fluorescent anti -counterfeit label materials, and use the visible launch of ER3+and YB3+ions to achieve a transformation from red to green, and in different power of different power Different luminous characteristics are displayed under laser irradiation.
The identification ability and stability of dynamic fluorescent anti-counterfeiting label materials have been improved, which can effectively prevent forgery and copying. The preparation method is simple and suitable for large-scale production.
Smart Images

Figure CN119331619A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of fluorescent anti-counterfeiting materials, and in particular to a dynamic fluorescent anti-counterfeiting label material and a preparation method and application thereof. Background Art
[0002] With the continuous development of social economy and science and technology, the problem of counterfeit and inferior products has become more and more serious, causing serious damage to consumer rights and social and economic order. The development of an efficient and reliable anti-counterfeiting technology has become an urgent problem to be solved. Upconversion luminescence is a luminescence phenomenon in rare earth doped nanocrystalline materials, such as NaYF4: Yb 3+ , Er 3+ In nanoparticles, Yb 3+ and Er 3+ Ion doping enables the material to achieve upconversion luminescence through a variety of mechanisms, including excited state absorption (ESA), energy transfer (ET), cooperative sensitization (CS), cross relaxation (CR), etc. 3+ Ions usually act as sensitizers to absorb near-infrared light and transfer energy to Er 3+ Ion, Er 3+ The ions then radiatively transition back to the ground state, emitting visible light, such as red and green.
[0003] At present, upconversion luminescent materials based on lanthanide ion doping have great application potential in the field of anti-counterfeiting due to their advantages such as long fluorescence lifetime, narrow emission band, and tunable spectrum. However, existing lanthanide-doped upconversion luminescent anti-counterfeiting materials have problems such as weak recognition ability and low stability, which limit their practical applications. Therefore, the existing technology needs to be improved. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a method for solving the problems of weak recognition ability and low stability of lanthanide-doped up-conversion luminescent anti-counterfeiting materials.
[0005] The technical solution of this application is as follows:
[0006] In a first aspect of the present application, a method for preparing a dynamic fluorescent anti-counterfeiting label material is provided, comprising the steps of: mixing and grinding yttrium chloride, ytterbium chloride, erbium chloride, and sodium fluoride to obtain a mixture; calcining the mixture to obtain the dynamic fluorescent anti-counterfeiting label material; wherein the percentage of ytterbium chloride in the mixture is 10-50 mol%, and the percentage of erbium chloride in the mixture is 1-5 mol%.
[0007] Optionally, the percentage of yttrium chloride in the mixture is 45-89 mol%.
[0008] Optionally, the mixture further comprises a sodium salt and a potassium salt other than sodium fluoride, the sodium salt other than sodium fluoride comprises sodium chloride, and the potassium salt comprises potassium chloride.
[0009] Optionally, the molar ratio of the sodium salt to the potassium salt in the mixture is 1:1, the mass ratio of the sodium salt in the mixture to the mixture is 7:26, and the mass ratio of the potassium salt in the mixture to the mixture is 7:26.
[0010] Optionally, a co-solvent is added during the grinding process, and the co-solvent includes one of ethanol and deionized water.
[0011] Optionally, the calcination treatment is carried out under an inert atmosphere, the inert atmosphere includes one of nitrogen, helium and argon, and the flow rate of the inert atmosphere is 100-200 mL / min; the calcination treatment temperature is 300-800° C., and the calcination treatment time is 4-8 h.
[0012] Optionally, after the mixture is calcined, it is further washed and dried, and the washing step includes: washing with a detergent for multiple times and centrifuging, and the detergent includes one of ethanol and deionized water.
[0013] The second aspect of the present application provides a dynamic fluorescent anti-counterfeiting label material prepared by the above-mentioned method for preparing the dynamic fluorescent anti-counterfeiting label material.
[0014] Optionally, the chemical formula of the dynamic fluorescent anti-counterfeiting label material is NaYF4:xEr 3+ ,yYb 3+ ; wherein x=1-5mol%, y=10-50mol%.
[0015] The third aspect of the present application provides a use of the above-mentioned dynamic fluorescent anti-counterfeiting label material in the preparation of anti-counterfeiting labels.
[0016] Beneficial effects of this application:
[0017] The present invention adjusts the ratio of ytterbium (Yb) and erbium (Er) in the raw materials, and utilizes Er 3+ and Yb 3+The visible emission of ions, green upconversion luminescence can be observed at 510-560nm, and red upconversion luminescence can be observed at 650-680nm, so that the prepared dynamic fluorescent anti-counterfeiting label material can show different luminescence characteristics under laser irradiation of different powers, thereby realizing the luminescence color change from red to green, which is different from the luminescence color change from green to red in the prior art, and can effectively prevent counterfeiting and copying, and realize dynamic anti-counterfeiting that is difficult to copy. In addition, the raw materials in this application can be prepared by the solid phase molten salt method, the method is simple, and large-scale production can be carried out. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for describing the embodiments.
[0019] Figure 1 The photoluminescence spectrum of the dynamic fluorescent anti-counterfeiting label material provided in the embodiment of the present application under 980nm excitation light;
[0020] (a) The power density is 762.5 mW / cm 2 Photoluminescence spectrum under excitation; (b) is the power density of 13237.5mW / cm 2 Photoluminescence spectrum under excitation;
[0021] Figure 2 A red-to-green ratio curve of the dynamic fluorescent anti-counterfeiting label material provided in an embodiment of the present application under 980nm excitation light;
[0022] Figure 3 A red-green ratio curve of the comparative example material provided in the embodiment of the present application under 980nm excitation light;
[0023] Figure 4 This is an actual color diagram of the excitation light irradiation provided in the embodiment of the present application. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solutions and advantages of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the drawings and embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present application. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0025] It should be noted that if there are descriptions involving "first", "second", etc. in the implementation of this application, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance and implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the fact that ordinary technicians in the field can implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by this application.
[0026] In the prior art, upconversion luminescent materials based on lanthanide ion doping have great application potential in the field of anti-counterfeiting due to their advantages such as long fluorescence lifetime, narrow emission band, and tunable spectrum. However, existing lanthanide-doped upconversion luminescent anti-counterfeiting materials have problems such as weak recognition ability and low stability, which limits their practical application.
[0027] Based on this, a first aspect of an embodiment of the present application provides a method for preparing a dynamic fluorescent anti-counterfeiting label material, comprising the steps of:
[0028] S1. Mix and grind yttrium chloride, ytterbium chloride, erbium chloride and sodium fluoride to obtain a mixture. The percentage of ytterbium chloride in the mixture is 10-50 mol%, for example, the percentage of ytterbium chloride in the mixture is 10 mol%, 15 mol%, 20 mol%, 25 mol%, 30 mol%, 35 mol%, 40 mol%, 45 mol% or 50 mol%, etc. The percentage of erbium chloride in the mixture is 1-5 mol%, for example, the percentage of erbium chloride in the mixture is 1 mol%, 2 mol%, 3 mol%, 4 mol% or 5 mol%, etc.
[0029] Yttrium chloride provides Y 3+ ions, ytterbium trichloride provides Yb 3+ ions, erbium chloride provides Er 3+ Ions, by adjusting the percentage of yttrium chloride, ytterbium trichloride and erbium chloride, the prepared dynamic fluorescent anti-counterfeiting label can achieve a luminescent color change from red to green, and the color change is more obvious. The mixture of sodium salt and potassium salt reduces the melting point of the reaction during the preparation, thereby reducing the need for high temperature in the preparation process and reducing the preparation cost.
[0030] In some embodiments, the mixture also includes other sodium salts and potassium salts besides sodium fluoride. Other sodium salts besides sodium fluoride include sodium chloride, and potassium salts include potassium chloride. For example, sodium chloride and potassium chloride are mixed and ground with other raw materials (yttrium chloride, ytterbium chloride, erbium chloride, sodium fluoride) to obtain a mixture.
[0031] In some embodiments, during the grinding in S1, a cosolvent may be added to the mixture of yttrium chloride, ytterbium chloride, erbium chloride, sodium salt and potassium salt, and the cosolvent includes one of ethanol and deionized water. The cosolvent is added during the grinding process to help reduce the viscosity of the components, improve the efficiency of mixing, and make the components mixed more evenly. The cosolvent will evaporate during the grinding process and will not enter the mixture. If the cosolvent is not completely evaporated, a drying operation can be performed after grinding to further remove the cosolvent.
[0032] In some embodiments, the percentage of yttrium chloride in the mixture is 45-89 mol%, for example, the molar proportion of yttrium chloride in the mixture is 45 mol%, 50 mol%, 55 mol%, 60 mol%, 65 mol%, 70 mol%, 75 mol%, 80 mol%, 85 mol%, 87 mol% or 89 mol%, etc. The molar ratio of sodium salt to potassium salt is 1: 1. In some embodiments, the mass ratio of sodium salt to mixture is 7:26, and the mass ratio of potassium salt to mixture is 7:26.
[0033] S2, calcining the mixture in S1, washing and drying the calcined mixture to obtain a dynamic fluorescent anti-counterfeiting label material.
[0034] In some embodiments, the calcination treatment is carried out under an inert atmosphere, and the inert atmosphere includes one of nitrogen, helium, and argon. By calcining under an inert atmosphere, most of the oxygen can be isolated, and the components can be prevented from spontaneous combustion or oxidation reaction during the calcination process, the generation of impurities can be reduced, and the yield of the final product can be improved. The gas flow rate of the inert atmosphere is 100-200mL / min, for example, the gas flow rate of the inert atmosphere is 100mL / min, 120mL / min, 140mL / min, 150mL / min, 160mL / min, 180mL / min or 200mL / min, etc.
[0035] In some embodiments, the calcination temperature is 300-800° C., for example, the calcination temperature is 300° C., 400° C., 500° C., 600° C., 700° C., or 800° C. The calcination time is 4-8 hours, for example, the calcination time is 4 hours, 5 hours, 6 hours, 7 hours, or 8 hours.
[0036] In some embodiments, the cleaning step includes: cleaning with a detergent multiple times and centrifuging. The detergent includes one of ethanol and deionized water. The detergent cleaning can remove unreacted components and impurities, and the detergent remaining on the surface can be removed by centrifugation, thereby removing or reducing impurities on the dynamic fluorescent anti-counterfeiting label material obtained after drying, which is convenient for subsequent processing and use. A large amount of water is removed by drying, reducing the probability of deliquescence or oxidation. The stability of the dynamic backlight anti-counterfeiting label material is improved.
[0037] According to a second aspect of the embodiments of the present application, there is provided a dynamic fluorescent anti-counterfeiting label material prepared by the method for preparing the dynamic fluorescent anti-counterfeiting label material in the embodiments of the present application.
[0038] The nanocrystals in the dynamic fluorescent anti-counterfeiting label material prepared in the examples of the present application can exhibit different luminescence characteristics under different powers of excitation light, which can be used to design complex anti-counterfeiting patterns or codes, which can only be correctly identified under specific excitation conditions, thereby effectively preventing forgery and copying. At the same time, the chemical stability and light stability of the nanocrystals ensure the durability and reliability of the anti-counterfeiting mark under different environmental conditions, and can maintain its anti-counterfeiting function even in harsh environments.
[0039] In some embodiments, the chemical formula of the dynamic fluorescent anti-counterfeiting label material is NaYF4:xEr 3+ ,yYb 3+ ; x, y represent Er 3+ and Yb 3+ The doping amount in NaYF4 is specifically, x=1-5 mol%, y=10-50 mol%. The dynamic fluorescent anti-counterfeiting label material (NaYF4: xEr 3+ ,yYb 3+ )Er in nanocrystals 3+ and Yb 3+ Visible emission, green upconversion (UC) emission can be observed at 510-560nm, corresponding to Er 3+ from 2 H 11 / 2 , 4 S 3 / 2 Energy level to 4 I 15 / 2 energy level transition; red UC emission can be observed at 640-680nm, corresponding to Yb 3+ from 4 F 9 / 2 Energy level to 4 I 15 / 2 Energy level state transition.
[0040] In some embodiments, the dynamic fluorescent anti-counterfeiting label material prepared in the examples of the present application changes its luminous color from red to green as the power of the excitation light increases. Different from other materials that achieve up-conversion color change from green to red as the excitation power increases, the dynamic fluorescent anti-counterfeiting label material prepared in the examples of the present application easily achieves a luminous color change from red to green, thereby achieving dynamic anti-counterfeiting that is difficult to replicate.
[0041] According to a third aspect of the embodiments of the present application, there is provided a use of the above-mentioned dynamic fluorescent anti-counterfeiting label material in the preparation of an anti-counterfeiting label.
[0042] Fluorescent anti-counterfeiting labels are an anti-counterfeiting technology that uses ultraviolet light for identification. Its main feature is that it uses special fluorescent materials to print fixed text, patterns or mobile numbers on the label. This information cannot be found by the naked eye or touch, and must be illuminated by ultraviolet light (fluorescent light) to be seen by the naked eye. Fluorescent anti-counterfeiting labels have extremely high concealment and concealment, and are widely used in various fields that require anti-counterfeiting protection.
[0043] In some embodiments, the dynamic fluorescent anti-counterfeiting label material can be plastic-sealed when it is made into a label, and the air can be isolated by the plastic sealing to make it more durable and stable.
[0044] In some embodiments, the fluorescent anti-counterfeiting label includes at least one of text, patterns, and numbers.
[0045] The following is further described by means of specific examples.
[0046] Example 1
[0047] Weigh 0.383g of yttrium chloride, 0.381g of ytterbium chloride, 0.382g of erbium chloride, 0.336g of sodium fluoride, 0.7g of potassium chloride, and 0.7g of sodium chloride into a mortar, add ethanol in small amounts and grind, dry to remove excess ethanol, and transfer to a quartz container. Place the quartz container in a muffle furnace at 150m 3 Nitrogen was introduced at a flow rate of / min and calcined at 300°C for 8h. After the calcination, the product was cooled to room temperature and washed with ethanol. After washing, the residual ethanol was removed by centrifugation. This process was repeated three times. Finally, the product was dried to obtain a dynamic fluorescent anti-counterfeiting label material, which was stored for later use.
[0048] Example 2
[0049] Weigh 0.339 g of yttrium chloride, 0.572 g of ytterbium chloride, 0.191 g of erbium chloride, 0.336 g of sodium fluoride, 0.7 g of potassium chloride, and 0.7 g of sodium chloride into a mortar, add ethanol in small amounts and grind, dry to remove excess ethanol, and transfer to a quartz container. Place the quartz container in a muffle furnace at 150 m3 Nitrogen was introduced at a flow rate of / min and calcined at 500°C for 6h. After the calcination, the product was cooled to room temperature and washed with ethanol. After washing, the residual ethanol was removed by centrifugation. This process was repeated 3 times. Finally, the product was dried to obtain a dynamic fluorescent anti-counterfeiting label material, which was stored for later use.
[0050] Example 3
[0051] Weigh 0.231 g of yttrium chloride, 0.954 g of ytterbium chloride, 0.573 g of erbium chloride, 0.336 g of sodium fluoride, 0.7 g of potassium chloride, and 0.7 g of sodium chloride into a mortar, add ethanol in small amounts and grind, dry to remove excess ethanol, and transfer to a quartz container. Place the quartz container in a muffle furnace at 150 m 3 Nitrogen was introduced at a flow rate of / min and calcined at 800°C for 4h. After the calcination, the product was cooled to room temperature and washed with ethanol. After washing, the residual ethanol was removed by centrifugation. This process was repeated 3 times. Finally, the product was dried to obtain a dynamic fluorescent anti-counterfeiting label material, which was stored for later use.
[0052] Comparative Example 1
[0053] Weigh 0.417 g of yttrium chloride, 0.191 g of ytterbium chloride, 0.954 g of erbium chloride, 0.336 g of sodium fluoride, 0.7 g of potassium chloride, and 0.7 g of sodium chloride into a mortar, add ethanol in small amounts and grind, dry to remove excess ethanol, and transfer to a quartz container. Place the quartz container in a muffle furnace at 150 m 3 Nitrogen was introduced at a flow rate of / min and calcined at 800°C for 4h. After the calcination, the product was cooled to room temperature and washed with ethanol. After washing, the residual ethanol was removed by centrifugation. This process was repeated 3 times. Finally, the product was dried to obtain a dynamic fluorescent anti-counterfeiting label material, which was stored for later use.
[0054] Test Example 1
[0055] The dynamic fluorescent anti-counterfeiting label material prepared in Example 1 was subjected to photoluminescence spectroscopy (PL) analysis.
[0056] Lay the quartz glass sheet flat in the groove of the tablet pressing mold, evenly disperse the ground dynamic fluorescent anti-counterfeiting label material prepared in Example 1 on the glass sheet, cover the knob on the groove, and make a mold containing the sample to be tested. Install the mold on the emission spectrum scanner and perform fluorescence testing. The test results are as follows: Figure 1 As shown. Among them, Figure 1 (a) shows a power density of 762.5 mW / cm 2Photoluminescence spectrum under excitation; (b) is the power density of 13237.5mW / cm 2 Photoluminescence spectrum under excitation. From (a) and (b), it can be seen that at a power density of 762.5 mW / cm 2 Under the excitation light of 980nm, the dynamic fluorescent anti-counterfeiting label material in Example 1 has a large peak at 640-680nm, indicating that the dynamic fluorescent anti-counterfeiting label material in Example 1 has a large peak at 762.5mW / cm 2 The 980nm excitation light emits red light at a power density of 12237.5mW / cm 2 Under the excitation light of 980nm, the dynamic fluorescent anti-counterfeiting label material in Example 1 has a large peak at 510-560nm, indicating that the dynamic fluorescent anti-counterfeiting label material in Example 1 has a large peak at 12237.5mW / cm 2 The dynamic fluorescent anti-counterfeiting label material in Example 1 emits green light under the excitation light of 980 nm, that is, the dynamic fluorescent anti-counterfeiting label material in Example 1 realizes an up-conversion color change from red to green as the excitation power increases, and changes from red to green, so as to realize dynamic anti-counterfeiting that is difficult to copy.
[0057] Test Example 2
[0058] (1) The dynamic fluorescent anti-counterfeiting label material prepared in Example 1 was subjected to PL analysis at 980 nm excitation light and different power densities, and the ratio of red light to green light was calculated. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that as the excitation light power density increases, the red-green light ratio decreases significantly, indicating that the dynamic fluorescent anti-counterfeiting label material in Example 1 achieves an up-conversion color transition from red to green as the excitation power increases.
[0059] (2) The material prepared in Comparative Example 1 was subjected to PL analysis at 980 nm excitation light and different power densities, and the ratio of red light to green light was calculated. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that when the excitation light power is low, the red-green light ratio of the material prepared in Comparative Example 1 is very low, and the overall display is green, and as the excitation light power density increases, the overall trend is still downward. Therefore, Comparative Example 1 cannot achieve the color change from red light to green light.
[0060] Test Example 3
[0061] The dynamic fluorescent anti-counterfeiting label material prepared in Example 1 was tested for illumination in actual scenes. The prepared dynamic fluorescent anti-counterfeiting label material was ground into powder, laid out on a black plane to form the word "SZTU" and fixed, and a laser transmitter was used to illuminate the word "SZTU" at different distances to observe the luminescence of the word "SZTU". The results are as follows: Figure 4 As shown. Figure 4 It can be seen that when irradiated at a distance of about 12 cm, the dynamic fluorescent anti-counterfeiting label material emits red light, when irradiated at a distance of about 6-8 cm, the dynamic fluorescent anti-counterfeiting label material emits green light, and when irradiated at a distance of about 8-12 cm, the dynamic fluorescent anti-counterfeiting label material emits yellow light. That is, the dynamic fluorescent anti-counterfeiting label material prepared in Example 1 changes from emitting red light to emitting yellow light (the superposition effect of red light and green light), and then to emitting green light as the power of the excitation light increases (achieved by adjusting the distance between the laser source and the material), and color change can be achieved.
[0062] It can be seen from the test examples that the dynamic fluorescent anti-counterfeiting label material prepared in Example 1 changes its luminous color between red, yellow and green as the power of the excitation light increases, and can be made into a dynamic fluorescent anti-counterfeiting label that can achieve dynamic anti-counterfeiting that is difficult to copy.
[0063] In summary, the present invention adjusts the ratio of ytterbium (Yb) and erbium (Er) in the raw materials and utilizes Er 3+ and Yb 3+ The visible emission of ions, green upconversion luminescence can be observed at 510-560nm, and red upconversion luminescence can be observed at 650-680nm, so that the prepared dynamic fluorescent anti-counterfeiting label material can show different luminescence characteristics under laser irradiation of different powers, thereby realizing the luminescence color change from red to green, which can be used to make complex anti-counterfeiting patterns or codes, effectively prevent forgery and copying, and realize dynamic anti-counterfeiting that is difficult to copy. In addition, the present application can be prepared by the solid phase molten salt method, the method is simple, and can be mass-produced.
[0064] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to this application.
Claims
1. A method for preparing a dynamic fluorescent anti-counterfeiting label material, characterized in that: Includes steps: Mixing and grinding yttrium chloride, ytterbium chloride, erbium chloride, and sodium fluoride to obtain a mixture; calcining the mixture to obtain the dynamic fluorescent anti-counterfeiting label material; The percentage of ytterbium trichloride in the mixture is 10-50 mol%, and the percentage of erbium chloride in the mixture is 1-5 mol%.
2. The preparation method according to claim 1, characterized in that: The percentage of yttrium chloride in the mixture is 45-89 mol%.
3. The preparation method according to claim 1, characterized in that: The mixture also includes sodium salts other than sodium fluoride and potassium salts, wherein the sodium salt other than sodium fluoride includes sodium chloride and the potassium salt includes potassium chloride.
4. The preparation method according to claim 3, wherein the molar ratio of the sodium salt to the potassium salt in the mixture is 1:1, the mass ratio of the sodium salt in the mixture to the mixture is 7:26, and the mass ratio of the potassium salt in the mixture to the mixture is 7:
26.
5. The preparation method according to claim 4, characterized in that: A co-solvent is added during the grinding process, and the co-solvent includes one of ethanol and deionized water.
6. The preparation method according to claim 1, characterized in that: The calcination treatment is carried out under an inert atmosphere, wherein the inert atmosphere includes one of nitrogen, helium and argon, and the gas flow rate of the inert atmosphere is 100-200 mL / min; The calcination temperature is 300-800°C, and the calcination time is 4-8h.
7. The preparation method according to claim 1, characterized in that: After the mixture is calcined, it is washed and dried. The washing step includes: washing with a detergent for multiple times and centrifuging. The detergent includes one of ethanol and deionized water.
8. A dynamic fluorescent anti-counterfeiting label material prepared by the preparation method according to any one of claims 1 to 7.
9. The dynamic fluorescent anti-counterfeiting label material according to claim 8, characterized in that: The chemical formula of the dynamic fluorescent anti-counterfeiting label material is NaYF4:xEr 3+ ,yYb 3+ ; wherein x=1-5mol%, y=10-50mol%.
10. Use of the dynamic fluorescent anti-counterfeiting label material prepared by the preparation method according to any one of claims 1 to 5 in preparing anti-counterfeiting labels.